2016
DOI: 10.1038/srep21399
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis of the kiwifruit canker pathogen Pseudomonas syringae pv. actinidiae biovar 5

Abstract: Pseudomonas syringae pv. actinidiae (Psa) is a destructive pathogen of kiwifruit bacterial canker disease, causing severe economic losses to kiwifruit industry worldwide. Biovar 5 is the most recently reported biovar of Psa, and is found in only a local area of Japan at present. There is not much information of genetic characteristics of biovar 5. Thus, the genome of biovar 5 was sequenced and analyzed to clarify its detailed genetic characteristics. Here, the genomes of strain MAFF 212056 and MAFF 212061 of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 19 publications
(58 reference statements)
2
92
0
2
Order By: Relevance
“…A number of strategies for canker disease control have been presented (Reglinski et al, 2013); however, none have been shown to be effective in inhibiting Psa from invading into kiwifruit host tissues and cells, and this may be partly due to our limited understanding of its host-pathogen molecular interactions. Based on phylogenetic analysis, Psa strains can be grouped into five biovars (Biovars 1–5; Fujikawa and Sawada, 2016), in which biovar 3 has the high virulence and is the causative agent of the current outbreaks of kiwifruit canker disease. Previous research investigations have revealed that plant recognition receptors proteins (PRRs) genes, resistance (R) genes, and transcriptional factors (TFs) significantly affect plant immune responses to pathogen invasion (Chisholm et al, 2006; Pandey and Somssich, 2009; Kazan and Lyons, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A number of strategies for canker disease control have been presented (Reglinski et al, 2013); however, none have been shown to be effective in inhibiting Psa from invading into kiwifruit host tissues and cells, and this may be partly due to our limited understanding of its host-pathogen molecular interactions. Based on phylogenetic analysis, Psa strains can be grouped into five biovars (Biovars 1–5; Fujikawa and Sawada, 2016), in which biovar 3 has the high virulence and is the causative agent of the current outbreaks of kiwifruit canker disease. Previous research investigations have revealed that plant recognition receptors proteins (PRRs) genes, resistance (R) genes, and transcriptional factors (TFs) significantly affect plant immune responses to pathogen invasion (Chisholm et al, 2006; Pandey and Somssich, 2009; Kazan and Lyons, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory effects of the fermentation broth of Actinomycete A217 on pathogenic bacteria were determined using the agar diffusion method (Peela et al ). A 100 ml portion of melted NA (Fujikawa and Sawada ) bacterial culture medium was cooled to 45°C, following which, 10–15 ml of NA was added to the logarithmic growth phase of the tested pathogenic bacterial liquid, which was fully shaken. Each dish (90 mm in diameter) was cultured with 15 ml of carrier medium.…”
Section: Methodsmentioning
confidence: 99%
“…juglandis and Kiwifruit canker caused by Pseudomonas syringae pv. actinidae also cause serious losses to the fruit industry (Lang and Evans ; Fujikawa and Sawada ).…”
Section: Introductionmentioning
confidence: 99%
“…actinidiae biovars and related pathovars. Gene organization of the regions (Genka et al ., ; Sawada et al ., ; Fujikawa & Sawada, , ) is schematically shown. The genes in the homologous relationship are connected by grey boxes.…”
Section: Psa Biovars Found In Japan and Their Characteristicsmentioning
confidence: 99%